2023
DOI: 10.1186/s12931-023-02393-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation after severe exacerbation of COPD: a nationwide population study

Abstract: Background Acute exacerbations of chronic obstructive pulmonary disease (COPD) lead to a significant reduction in quality of life and an increased mortality risk. Current guidelines strongly recommend pulmonary rehabilitation (PR) after a severe exacerbation. Studies reporting referral for PR are scarce, with no report to date in Europe. Therefore, we assessed the proportion of French patients receiving PR after hospitalization for COPD exacerbation and factors associated with referral. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“… 14 , 16 , 17 , 18 Our study reported similar outcomes in terms of reduction of mortality and hospitalization risks among patients with COPD as those in previous studies on pulmonary rehabilitation, while the magnitude of relative risk reduction of mortality reported in these studies (range, 31%-42%) was larger than for the NAHC-Respiratory program. 32 , 33 , 34 , 35 This difference may primarily be caused by differences in their service packages and how patients were targeted. The NAHC-Respiratory program provided a mixture of self-management education, risk factor midifications, and rehabilitation services to patients with COPD at primary care settings whose baseline mortality risk was relatively low, while the pulmonary rehabilitation services reported in the literature primarily targeted more high-risk patients following their excerbations and hospitalizations with a baseline annual mortality rate ranging from 17.3% to 25.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 16 , 17 , 18 Our study reported similar outcomes in terms of reduction of mortality and hospitalization risks among patients with COPD as those in previous studies on pulmonary rehabilitation, while the magnitude of relative risk reduction of mortality reported in these studies (range, 31%-42%) was larger than for the NAHC-Respiratory program. 32 , 33 , 34 , 35 This difference may primarily be caused by differences in their service packages and how patients were targeted. The NAHC-Respiratory program provided a mixture of self-management education, risk factor midifications, and rehabilitation services to patients with COPD at primary care settings whose baseline mortality risk was relatively low, while the pulmonary rehabilitation services reported in the literature primarily targeted more high-risk patients following their excerbations and hospitalizations with a baseline annual mortality rate ranging from 17.3% to 25.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The NAHC-Respiratory program provided a mixture of self-management education, risk factor midifications, and rehabilitation services to patients with COPD at primary care settings whose baseline mortality risk was relatively low, while the pulmonary rehabilitation services reported in the literature primarily targeted more high-risk patients following their excerbations and hospitalizations with a baseline annual mortality rate ranging from 17.3% to 25.2%. 32 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Alec Bass, PT, PhD 1 ; Sarah Géphine, PhD 2,3 ; Mickaël Martin, MSc 1 ; Marianne Belley, BSc 1 ; Manon Robic, MSc 3 ; Claudine Fabre, Pr 3 ; Jean-Marie Grosbois, MD 2 ; Geneviève Dion, MD 1 ; Didier Saey, PT, PhD 1 ; Arnaud Chambellan, MD 4 ; François Maltais, MD Corresponding author: Dr François Maltais, Centre de recherche de l'Institut universitaire de cardiologie et de pneumologie de Québec (CR-IUCPQ), Québec, Canada, G1V 4G5, francois.maltais@fmed.ulaval.ca…”
Section: Assessing Functional Capacity In Directly and Remotely Monit...unclassified
“…Unfortunately, access to rehabilitation care remains limited in many countries, including in Canada and France. Indeed, latest available estimates indicate that only 0.4% of individuals in Canada and 8.6% of individuals in France with COPD have access to pulmonary rehabilitation programs [2,3]. The development of new and innovative healthcare models, including in rehabilitation, is urgently needed to address this healthcare gap that is only expected to worsen with the aging populations in most advanced economies [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…At a time when access to PR represents a major challenge in the management of individuals with COPD [ 5 , 6 ], home- or community-based interventions requiring minimal equipment may provide valuable alternatives to in-patient PR programs [ 7 , 8 ]. The 6-min walking test (6-MWT) is currently the most validated and widely used field test for evaluating exercise capacity in patients undergoing PR, but its application remains complex [ 9 ].…”
Section: Introductionmentioning
confidence: 99%